Constitutional-legal aspects of information security in the context of globalization - Farzullaeva, Afat Elkhan (ScienceRise: Juridical Science, 2022)
One of the main issues of world politics since the 21st century is a scientific and technological breakthrough that can have far-reaching consequences in all areas of human activity. The computerization and information revolution have led to scientific and technological progress in the military field. The application of high technology has radically changed the nature and capabilities of conventional armaments, intelligence and military command systems, and expanded the possibilities of long-distance warfare. Today, the tactics of creating conflicts in many military and other fields with the help of information technology are changing in the world. Who controls information and misinformation plays an important role. Sometimes misinformation becomes a dangerous weapon. Although the existing terms "Information Security" and "Information War" are more commonly used in the military field, they are beginning to take on a slightly different meaning with the development of mass media and communication technologies. This article identifies the legal characteristics and legal specifics of the information rights of citizens, proclaimed by the Constitution of Azerbaijan. The article substantiates the need to consider the constitutional and legal foundations of information security as a complex political and legal phenomenon. It is proposed to analyze the constitutional and legal aspects of information security in the synthesis of constitutional ideology, constitutional theory and constitutional practice of the development of Azerbaijani statehood. The author proves that the constitutional legal provision of the information security of Azerbaijan considers positive international experience in this field